Cellular Blue Nevus Diagnosed following Excision of Melanoma: A Challenge in Diagnosis - Nives Jonjić; Andrea Dekanić; Nedeljka Glavan; Larisa Prpić-Massari; Blaženka Grahovac (Hindawi Limited, 2016)
A case of a 41-year-old woman with a history of nodular melanoma (NM), associated with an indurated dome-shaped blue-black nodule with a diameter of 1.2 cm in the gluteal region, is presented. Clinical diagnosis of the lesion, present from birth, was blue nevus. Recently, the nodule has been showing a mild enlargement and thus complete resection was performed. Histological analysis revealed a pigmented lesion with an expansive pattern of extension into the dermis and the subcutaneous adipose tissue. The lesion displayed an alveolar pattern as well as a pigmented dendritic cell pattern. The histology was consistent with cellular blue nevus (CBN); however, the history of NM which was excised one year earlier, as well as the clinical information about the slow growing lesion, included a differential diagnosis of CBN, borderline melanocytic tumor, and malignant blue nevus. Additional immunohistochemical (HMB-45, p16, and Ki-67) and molecular (BRAF V600E mutation) analyses were performed on both lesions: the CBN-like and the previously excised NM. Along with lesion history and histological analyses, p16 staining and BRAF were useful diagnostic tools for confirming the benign nature of CBN in this case.